Efficacy and safety of topical acetylcysteine combined with the use of an overcurvature-correcting device in patients with pincer nail deformity: a randomized, vehicle-controlled, investigator-blinded study - Masataka Saito; Akihiko Ikoma; Akira Fujikawa; Kazuaki Tanaka (Taylor & Francis Group, 2023)
Background While pincer nails may be treated using overcurvature-correcting devices, it takes several months to achieve successful outcomes. Nail-softening drugs may reduce the treatment duration required. Objective To evaluate the efficacy and safety of treatment with acetylcysteine (AC) gel added to an overcurvature-correcting device, and define the optimal AC concentration. Methods In this investigator-blinded study, 70 patients with hallux pincer nail were fitted with an overcurvature-correcting device for 7 days and were randomly assigned to receive a single 24-h administration of a gel containing 10%, 20% or 30% AC or vehicle. Nail improvement was objectively evaluated by calculating the distal narrowed nail width (dNNW) ratio. Results All three AC concentrations plus device showed earlier sustained improvement of pincer nails versus vehicle plus device. There was no observable correlation between AC concentration and effectiveness. No clinically problematic adverse events were observed at any AC concentration, and we recommended AC gel at a concentration of 10%. Conclusions By adding AC gel application to an overcurvature-correcting device, early and sustained reductions in transverse curvature were produced compared with using a device alone (vehicle control). The dNNW ratio used in this study was an appropriate objective index for evaluating therapeutic effects.